A Petrov-Galerkin finite element method for 2D transient and steady state highly advective flows in porous media. (August 2018) - Cui, W.; Gawecka, K.A.; Potts, D.M.; Taborda, D.M.G.; Zdravković, L.
Abstract: A new Petrov-Galerkin finite element method for two-dimensional (2D) highly advective flows in porous media, which removes numerical oscillations and retains its precision compared to the conventional Galerkin finite element method, is presented. A new continuous weighting function for quadratic elements is proposed. Moreover, a numerical scheme is developed to ensure the weighting factors are accurately determined for 2D non-uniform flows and 2D distorted elements. Finally, a series of numerical examples are performed to demonstrate the capability of the approach. Comparison against existing methods in the simulation of a benchmark problem further verifies the robustness of the proposed method.